Exploring the Mechanism of Indigo Naturalis in the Treatment of Ulcerative Colitis Based on TLR4/MyD88/NF-κB Signaling Pathway and Gut Microbiota - Yang, Qi-yue; Ma, Le-le; Zhang, Chen; Lin, Jun-zhi; Han, Li; He, Ya-nan; Xie, Chun-guang (Frontiers in Pharmacology, 2021)
Background: Clinical trials have proved that indigo naturalis is a candidate drug for treating ulcerative colitis (UC), but its therapeutic mechanism is still unclear. Purpose: This study aimed to evaluated the protective effect and mechanism of indigo naturalis to treat mice with dextran sulfate sodium (DSS)-induced UC. Methods: DSS-induced UC mice were treated with indigo naturalis (200 mg/kg), indigo (4.76 mg/kg) and indirubin (0.78 mg/kg) for one week. The anti-UC mechanism of indigo naturalis were studied by pathological section, inflammatory factor, western blot and 16S rRNA sequencing. Results: Taking body weight change, disease activity index and colon length as indexes, indigo naturalis had the strongest anti DSS-induced UC effect, followed by indirubin and indigo. Pathological section showed that indigo naturalis, indigo and indirubin could reduce the infiltration of inflammatory cells, increase the secretion of intestinal mucus and repair the intestinal mucosa. Indigo naturalis, indigo and indirubin could reduce IL-1β，IL-6 and TNF-α by inhibiting TLR4/MyD88/NF-κB signal transduction. Indigo naturalis and indigo could also reduce IgA and IgG both in serum and colon tissue. In addition, indigo naturalis, indigo and indirubin could adjust the gut microbiota structure of DSS-induced UC mice, namely reduce the ratio of Firmicutes/Bacteroidetes and increase the abundance of probiotics. Conclusions: Indigo and indirubin are one of the main anti-UC components of indigo naturalis. The anti-UC mechanism of indigo naturalis may be through inhibiting TLR4/MyD88/NF-κB signal transduction and regulating gut microbiota.